Pelindungan Hukum Bagi Konsumen Yang Menjadi Korban Perusahaan Investasi Ilegal Berbasis Multi Level Marketing - Jennifer Clarence; Heru Sugiyono (Jurnal USM Law Review)
This study aims to analyze legal protection and compensation mechanisms for consumers who are victims of illegal MLM-based investments, referring to Law Number 8 of 1999, and to assess the role and effectiveness of the OJK in supervision and enforcement. This illegal investment phenomenon is relevant to study because it often utilizes manipulative tactics, including the use of misleading information to encourage potential consumers to allocate their funds. Although legal regulations related to consumer protection are available, effective implementation and supervision are often challenges in ensuring that victims receive fair compensation. The study uses a normative legal method by reviewing theories, concepts, legal principles, and related laws and regulations. The research findings show that victims of illegal MLM-based investments in Indonesia have legal protection under the Consumer Protection Law, with supervision carried out by the Financial Services Authority (OJK). Victims have the right to file for a refund or compensation through a class action lawsuit mechanism. However, the limited assets of the perpetrator company are a major obstacle in implementing compensation. Therefore, a new, more effective approach is needed in supervision and law enforcement, including improving regulations to mitigate similar risks in the future.